Acute electrocardiographic changes during smoking: an observational study. Issue 4 (5th April 2013) - Ramakrishnan, Sivasubramanian; Bhatt, Kinjal; Dubey, Akhilesh K; Roy, Ambuj; Singh, Sandeep; Naik, Nitish; Seth, Sandeep; Bhargava, Balram
Abstract : Objective: To study the temporal relationship of smoking with electrophysiological changes. Design: Prospective observational study. Setting: Tertiary cardiac center. Participants: Male smokers with atypical chest pain were screened with a treadmill exercise test (TMT). A total of 31 such patients aged 49.8±10.5 years, in whom TMT was either negative or mildly positive were included. Heart rate variability (HRV) parameters of smokers were compared to those of 15 healthy non-smoking participants. Interventions: All patients underwent a 24 h Holter monitoring to assess ECG changes during smoking periods. Results: Heart rate increased acutely during smoking. Mean heart rate increased from 83.8±13.7 bpm 10 min before smoking, to 90.5±16.4 bpm during smoking, (p<0.0001) and returned to baseline after 30 min. Smoking was also associated with increased ectopic beats (mean of 5.3/h prior to smoking to 9.8/h during smoking to 11.3/h during the hour after smoking; p<0.001). Three patients (9.7%) had significant ST–T changes after smoking. HRV index significantly decreased in smokers (15.2±5.3) as compared to non-smoking controls participants (19.4±3.6; p=0.02), but the other spectral HRV parameters were comparable. Conclusions: Heart rate and ectopic beats increase acutely following smoking. Ischaemic ST–T changes were also detected during smoking. Spectral parameters of HRV analysis of smokers remained in normal limits, but more importantly geometrical parameter—HRV index—showed significant abnormality.